IMPLEMENTATION OF HAVERSINE FORMULA IN AN ANDROID-BASED GEOGRAPHIC INFORMATION SYSTEM BPJS HEALTH FACILITIES IN PURWAKARTA - Irgiyansyah; Nugroho, Imam Ma’ruf; Defriani, Meriska (RISTEC : Research in Information Systems and Technology, 2025)
This study designs and develops an Application Android-based Geographic Information System (GIS) to assist residents of Purwakarta Regency in locating the nearest BPJS-affiliated healthcare facilities, addressing the limitations of distance information and mapping on the Health Office’s website. To compute distances, the application utilizes the Haversine Formula based on the user’s coordinates. It is developed using Flutter for the Android application and Laravel for the web-based admin system, following the Extreme Programming (XP) methodology. Blackbox Testing is used to ensure system functionality. As a result, the application can display a list and geographic locations of healthcare facilities along with the distance from the user. The application is expected to provide easier access to healthcare information and enhance the quality of health services in Purwakarta Regency.